2018
DOI: 10.29309/tpmj/2018.25.02.456
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome

Abstract: Objectives: The objective of this study was to investigate the importance ofindividual IHD risk factors and major components of the metabolic syndrome associated withIHD. Study Design: Descriptive cross sectional study. Setting: Cardiology Department ofGulab Devi Chest Hospital Lahore. Period: Nov, 2015 to Feb, 2016. Methodology: Patientsof either gender and from 20 to 90 year of age admitted with IHD via emergency departmentwere recruited after informed consent. The frequency of metabolic syndrome was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Since its approval, rituximab's therapeutic indications were extended and presently include numerous other B-cell malignancies, autoimmune diseases, inflammatory disease, paraneoplastic pemphigus, pemphigus vulgaris, hypocomplementemic urticarial vasculitis, autoimmune cytopenias, and humoral organ transplant rejection. Rituximab is also prescribed for multicentric Castleman's disease and primary effusion lymphoma [11,25].…”
Section: Role Of Rituximab In Ks Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its approval, rituximab's therapeutic indications were extended and presently include numerous other B-cell malignancies, autoimmune diseases, inflammatory disease, paraneoplastic pemphigus, pemphigus vulgaris, hypocomplementemic urticarial vasculitis, autoimmune cytopenias, and humoral organ transplant rejection. Rituximab is also prescribed for multicentric Castleman's disease and primary effusion lymphoma [11,25].…”
Section: Role Of Rituximab In Ks Developmentmentioning
confidence: 99%
“…There is evidence, albeit limited, of the efficacy of treatment with valganciclovir. It was demonstrated that treatment with valganciclovir can reduce HHV-8 viral load and that valganciclovir can be used in high-risk patients to prevent KS flare [25]. Prophylactic treatment with valganciclovir can be administered to patients at high risk of developing KS.…”
Section: Management Of Rituximab-induced Ksmentioning
confidence: 99%
“…1 It is an FDA-approved drug for the management of autoimmune and lymphoproliferative disorders like Rheumatoid Arthritis (2), Pemphigus Vulgaris (PV), CD20 positive B-cell Non-Hodgkin's Lymphoma, and Chronic Lymphocytic Leukemia (CLL). [2][3][4] The off-label use of this treatment has also demonstrated efficacy in managing moderate to severe cases of mucous membrane pemphigoid (MMP). 5 Immediate infusion-related reactions including fever, cough, and dyspnea have been mentioned as a result of immunologic response.…”
Section: Introductionmentioning
confidence: 99%